THE THE POLICY IMPLEMENTATION OF CANDIDATION: Study of Golkar in Jambi City Mayoral Election 2024 - HM, Pahrudin; Lestari, Linayati; Abdi Muhammad, Hatta; Elviria, Samia; Senjaya, Burlian; Salman, Salman (Al-Risalah, 2025)
This study examines the Golkar Party's decision to nominate the Maulana-Diza pair over internal cadre, Budi Setiawan, for the 2024 Jambi City Mayoral Election using Mazmanian and Sabatier's policy implementation theory. The study highlights that candidate nomination serves as an internal party policy and that technical feasibility, strategic planning, and contextual responsiveness are necessary for its successful implementation. The study found that three primary factors influenced Golkar's choice: (1) The problem's substantive aspects, like Maulana-Diza's broader political coalition, increased electability, and preparedness for logistics; (2) The policy's goals' coherence and clarity, as demonstrated by Golkar's determination to maintain electoral dominance and internal cohesion; and (3) The political and socioeconomic background, including civil society involvement and post-pandemic recovery requirements. One crucial litmus test of Golkar's institutional development is the internal conflict arising from Budi Setiawan's exclusion. The party's ability to manage dissent, realign local loyalty, and preserve organisational unity demonstrates its capacity for successful policy implementation. According to the study's findings, political party nomination strategies guided by well-defined objectives, administrative readiness, and alignment with public needs are associated with effective public policy implementation. It demonstrates the effectiveness of policy implementation theory in evaluating internal party decision-making processes within democratic electoral systems.